(3GdbGfhf GdeSYhOis - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdMeOdI(B: (3GdHGH GdChd (B:(3aj eYQag CMhGd GdchGcH GdNeSg hMQcJgG hCadGcgG s
(3BNQgG (B:s
(3JfJgi HGdHG GdKGdK ef GdebGdI GdKGdKI s
(3ajgG LOGhd hQShe gfOSjIs
(3fSNI KGfjIs
(3fSNI ZjQ cGedg ZjQ efXeI JfJgi HGdHGH GdKGdK ef GdebGdg GdKGdKg hgh jSei gfG ai GdHYO Yf GdChJGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B79 s
Keywords: (3Gdadcs